The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/ncomms15223
|View full text |Cite|
|
Sign up to set email alerts
|

PTEN regulates glioblastoma oncogenesis through chromatin-associated complexes of DAXX and histone H3.3

Abstract: Glioblastoma (GBM) is the most lethal type of human brain cancer, where deletions and mutations in the tumour suppressor gene PTEN (phosphatase and tensin homolog) are frequent events and are associated with therapeutic resistance. Herein, we report a novel chromatin-associated function of PTEN in complex with the histone chaperone DAXX and the histone variant H3.3. We show that PTEN interacts with DAXX and, in turn PTEN directly regulates oncogene expression by modulating DAXX-H3.3 association on the chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 64 publications
5
85
0
2
Order By: Relevance
“…However, a recently published study demonstrated that PTEN also forms complexes with the histone chaperone DAXX and the histone variant H3.3, modulating chromatin association to regulate oncogene expression. This effect is independent of PTEN enzymatic activity (13). Congruent with these data, we noted that PTEN was present in both the cytosol and the nucleus ( Figure 3C).…”
Section: Case Study 2: Pten's Novel Function Through Chromatin-associsupporting
confidence: 82%
“…However, a recently published study demonstrated that PTEN also forms complexes with the histone chaperone DAXX and the histone variant H3.3, modulating chromatin association to regulate oncogene expression. This effect is independent of PTEN enzymatic activity (13). Congruent with these data, we noted that PTEN was present in both the cytosol and the nucleus ( Figure 3C).…”
Section: Case Study 2: Pten's Novel Function Through Chromatin-associsupporting
confidence: 82%
“…As HCMV seropositivity increases with age (Bate et al, 2010), perhaps pp71-mediated inactivation of Daxx precludes the need for mutation of this pathway in adults with HCMVpositive tumors. Recently, Daxx and the Phosphatase and Tensin homolog (PTEN) tumor suppressor were shown to have a synthetic lethal relationship in GBMs, where Daxx knockdown impaired tumor growth in PTEN-negative but not PTENpositive tumor cells (Benitez et al, 2017). Thus, it would be interesting to determine whether there is an inverse relationship between HCMV-positivity and PTEN mutation in adult GBMs.…”
Section: Pathogenesismentioning
confidence: 99%
“…Variants in the PTEN gene could also be useful in the personalisation of GBM treatment as mentioned previously; Han et al established a relationship between PTEN mutations and GBM patient survival [13]. Jiang et al demonstrated that PTEN mutations are associated with therapeutic resistance [31]; while Benitez et al demonstrated that PTEN regulates GBM oncogenesis [32]. Mutations in the PIK3R1gene have been shown to promote the growth and formation of gliomas [33], while PIK3CA missense mutations have been shown to promote GBM pathogenesis [34].…”
Section: Selection Of Mutated Genes For Personalisationmentioning
confidence: 99%